Improved learning outcomes of dribbling football through a game approach - Hengki Kumbara; Muhammad Tri Bintang Muharom; Dian Nuzulia (Universitas Sriwijaya, 2021)
The purpose of this study was to improve dribbling learning outcomes in soccer material. The research method that will be used in this study is a pre-experimental design with the treatment design in this study using a one-group pretest-posttest. The sample of this research is class XI IPS 1 which consists of 32 students. Determination of the sample using cluster random sampling technique. To assess dribbling ability is Soccer Battery. The results showed that there were differences in the dribbling abilities of students before and after giving treatment, namely learning with a game approach. Conclusion of this study is that learning with a play approach can improve students' dribbling learning outcomes in high school education units.